An efficient Mppt approach of PV systems: incremental conduction pathway - Murari Lal Azad; Pradip Kumar Sadhu; P Arvind; Anagh Gupta; Tuhin Bandyopadhyay; Soumya Das; Sabyasachi Samanta (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Distributed Generation source have wide application due to their phenomenal advantages. These sources include Photovoltaic (PV) cells producing DC voltage at their output that connects the network through a power electronic interface. PV characteristics, on the other hand, illustrate the fact that maximum power can be extracted at the optimal operating point depending upon the solar radiation and ambient temperature. In order to keep   the PV module at its optimal operating point, a DC-DC converter is often used between a PV module and inverter. Consequently, Maximum power point trackers (MPPT) grab the foremost position in the efficiency analysis of the global PV system. Among the several MPPT algorithms, Incremental Conduction technique isemphasised upon as it is extremely simple in implementation within electronic programmable circuits. This paper incorporates the MPPT model using a PV module that always works in its optimal operating point. Design and experimental results of a small prototype of MPPT is presented here based on the Simulink model to verify the advantages of proposed integrated system.